Longitudinal Assessment of Pulmonary Function and Bronchodilator Response in Pediatric Patients With Post-infectious Bronchiolitis Obliterans - Yu, Xiuhua; Wei, Jiaoyang; Li, Yanchun; Zhang, Lu; Che, Hongming; Liu, Li (Frontiers in Pediatrics, 2021)
Abstract Backgroud: Postinfectious bronchiolitis obliterans (PIBO) is a rare respiratory disease. In recent years, the disease has been recognized and diagnosed increasingly in children. Pulmonary function is important for diagnosis, identifying the severity of the PIBO and monitoring progression. But there have been only a few studies that followed the evolution of PIBO on the basis of pulmonary function tests (PFTs). Objective: The study targeted the evolution of pulmonary function and bronchodilator response in a case series of Chinese children with PIBO. Methods: Twelve children between the ages of 6-99months with PIBO were studied retrospectively from 2009 to 2019. Forced vital capacity (FVC), forced expiratory volume in 1 s (FEV1), the FEV1/FVC ratio, and maximal midexpiratory flow velocity 25%-75% (MMEF25%-75%) were collected at each PFT, and bronchodilator responses were evaluated. Spirometric parameters were monitored over time, and generalized linear mixed models were used to analyze longitudinal panel data. Results: The median baseline PFT values for FVC, FEV1, the FEV1/FVC ratio and MMEF25% -75% were 41.6%, 39.75%, 90.7% and 22.2%, respectively. At the initial PFTs, 10 (83.3%) patients demonstrated a significant bronchodilator response. FVC and FEV1 increased by 8.212%/year and 5.007%/year, respectively, and the FEV1/FVC ratio decreased by an average of 3.537%/year. MMEF25%-75% showed improvement at an average rate of 1.583% every year. Overall, FEV1 and MMEF25%-75% showed different degrees of improvement after the use of inhaled bronchodilators at each PFT session for 10 patients, and FEV1 measures demonstrated significant (>12%) β2-bronchodilation in 56% of PFT sessions. Conclusions: Pediatric patients with PIBO showed an obstructive defect in pulmonary function. The FVC, FEV1 and MMEF25%-75% improved as they grew older, while the FEV1/FVC ratio decreased. This may be due to the development of lung parenchyma more than airway growth. Airway obstruction in some patients improved with the use of β2 agonists.